PHYSIOLOGICAL ROLES AND ASSOCIATED DISORDERS OF ADIPONECTIN - Shrestha, Shailaza; Sharma, Preeti; Kumar, Pradeep; Sp, Saxena; Sharma, Rachna (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Among the adipokines, adiponectin is the first one to be described just over a decade ago. It is produced exclusively by adipose tissue and circulates in high concentration in human plasma accounting for 0.01% of proteins in plasma, almost thousand times higher than that of leptin. The normal circulating level of adiponectin ranges from 2 to 30 Âµg/ml. It is now observed that besides adipose tissue, adiponectin can also be produced by several other tissues such as hepatocytes, cardiomyocytes, and placenta. Adiponectin executes its action via autocrine as well as and paracrine effects. Researchers working in this area have revealed that adiponectin has insulin-sensitizing, anti-inflammatory and cardioprotective effects. Our review focuses on adiponectin, its mode Â of action on different peripheral tissues such as skeletal muscles, heart, liver, brain and its the correlative account in various diseases. Keywords: Adiponectin, Obesity, Type 2 diabetes, Inflammation, Malignancies, Cardiovascular disease.